(untitled) (Chimica nella Scuola, 2022)
We present an experiment for the determination of the pressure dependence of the chemical potential of dioxygen using a probe usually found in automobile combustion engines. The experiment is adapted to the needs of the high school in terms of cost and the ancillary equipment required; the apparatus is designed to promote clarity and educational understanding. Measurements show the logarithmic connection between the pressure of the gas and its chemical potential. The data are then successfully compared quantitatively with the theoretical prediction.